QUALITY IMPROVEMENT MANAGEMENT AT THE SENIOR HIGH SCHOOL MODEL IMPLEMENTING NATIONAL STANDARDIZED SCHOOL CATEGORY (SKM), LOCAL PROMINENCE BASED EDUCATION (PBKL), AND LEARNING RESOURCE CENTER (PSB) IN THE WEST NUSA TENGGARA - Furqan, Aidy; Bafadal, Ibrahim; *, Wahjoedi; Arifin, Imron (IJRDO- Journal of Educational Research, 2017)
The purpose of this qualitative research is to: (1) describing the process of formulating strategic plans in the quality improvement managementin school modelsimplementing National Standardized School Category (SKM), Local Prominence Based Education (PBKL) and Learning Resource Center (PSB);(2)describing the implementation of the quality improvement management in school models implementing National Standardized School Category (SKM), Local Prominence Based Education (PBKL) and Learning Resource Center (PSB) (3) describing how to organize the quality improvement management school models implementing National Standardized School Category (SKM), Local Prominence Based Education (PBKL) and Learning Resource Center (PSB) (4) describing the evaluation system in the quality improvement management school models implementing National Standardized School Category (SKM), Local Prominence Based Education (PBKL) and Learning Resource Center (PSB). This research was conducted by using both qualitative and quantitative approach. The data collected using qualitative method was aimed at providing enriched and complete information, as well as emphasizing the quantitative data. Data collection technique used interview instrument, field observation and documentation research. The data sources were the principals, the vice principals, the teachers, the high school models teams, the school boards and the students.